Cloning and expression analysis of the chitinase gene Ifu-chit2 from Isaria fumosorosea - Meng,Huimin (2015)
Entomopathogenic fungi can produce a series of chitinases, some of which function synergistically with proteases and other hydrolytic enzymes to degrade the insect cuticle. In the present study, the chitinase gene Ifu-chit2 from Isaria fumosorosea was investigated. The Ifu-chit2 gene is 1,435-bp long, interrupted by three short introns, and encodes a predicted protein of 423 amino acids with a 22 residue signal peptide. The predicted Ifu-Chit2 protein is highly homologous to Beauveria bassiana chitinase Bbchit2 and belongs to the glycohydrolase family 18. Ifu-Chit2 was expressed in Escherichia coli to verify chitinase activity, and the recombinant enzyme exhibited activity with a colloidal chitin substrate. Furthermore, the expression profiles of Ifu-chit2 were analyzed at different induction times under in vivo conditions. Quantitative real-time PCR analysis revealed that Ifu-chit2 expression peaked at two days post-induction. The expression of chitinase Ifu-chit2 in vivo suggests that the chitinase may play a role in the early stage of pathogenesis.